Protein enrichment of sweet potato by solid state fermentation using four mono-culture fungi (1999)
Washed, sliced and oven-dried whole sweet potato tubers (Ipomoea batatas) of the local variety were milled and supplemented with a mineral salts solution containing (g litre-1) glucose, 5; (NH4)2 SO4 1.5; KH2 PO4, 1.5; MgSO4 0.05;Yeast extract, 0.05 and fermented at 30ₒC for 72 hr by solid state fermentation (SSF) using Neurospora sitophila, Aspergillus niger, Candida utilis and Saccharomyces uvarum. At the end of the fermentation period A. niger gave the highest protein content of 11.8%, DM basis while S. uvarum showed the least protein content. However in terms of true protein production N sitophila gave the best value of 8.98%. While S. uvarum gave the least value under the Standard condition.